Answer:
Option (A)
Explanation:
Te given equation is,
-qx + p = r
Toe find the value of x,
By subtracting p from both the sides of the equation.
-qx + p - q = r - q
-qx = r - q
By dividing the whole equation by (-q),
![(-qx)/((-q))=(r-p)/(-q)](https://img.qammunity.org/2021/formulas/mathematics/high-school/y1ew305mxkbh9mbq012l1pj9zde2tkins9.png)
x =
![-(r-p)/(q)](https://img.qammunity.org/2021/formulas/mathematics/high-school/939yzkfo3547dw6bo2qz029xrjb9fnj7t7.png)
x =
![(p-r)/(q)](https://img.qammunity.org/2021/formulas/mathematics/high-school/2eek5su0rne6vvdk888scs9qoxbyi5spkd.png)
Therefore, Option (A) will be the answer.